Qualitative Analysis of the Effectiveness of the Communicative Learning Model in Arabic Language Instruction: Analisis Kualitatif Terhadap Efektivitas Model Pembelajaran Komunikatif Dalam Pembelajaran Bahasa Arab - Muflihah Az-Zahra; Isop Syafe'i (Jurnal Bahasa dan Sastra Pusaka Cendekia, 2025)
This study aims to analyze the effectiveness of the communicative learning model in improving students’ communicative competence, particularly in the aspects of maharah kalām (speaking skills) and maharah istimā’ (listening skills) in Arabic language learning. It also seeks to describe how the communicative model is implemented in the classroom and to identify the supporting and inhibiting factors that influence its effectiveness. In addition, this study attempts to explore teachers’ and students’ perceptions of the application of the communicative approach as part of efforts to enhance the quality of Arabic language learning. This research employs a qualitative approach using a library study design supported by primary data obtained from classroom observations, interviews with teachers and students, as well as documentation of learning instruments and classroom activities. Secondary data were collected from theories of Communicative Language Teaching (CLT), textbooks, and relevant previous studies. The data analysis procedures include data reduction, data display, interpretation of findings, and systematic conclusion drawing to obtain a comprehensive overview of the effectiveness of the communicative model in the context of Arabic language learning. The findings reveal that the communicative learning model is effective in improving students’ speaking and listening abilities through activities such as pair work, role-play, language games, group discussions, and the use of contextual media. Students became more confident, active, and able to comprehend meaning in real-life contexts. Both teachers and students demonstrated positive perceptions of this approach as it is more engaging and relevant to communicative needs. However, its effectiveness is influenced by limited vocabulary, feelings of shyness, language anxiety, inadequate learning facilities, and differences in students’ abilities, thereby requiring appropriate differentiation strategies. Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran komunikatif dalam meningkatkan kemampuan komunikatif peserta didik, terutama dalam aspek maharah kalām dan maharah istimā’ pada pembelajaran Bahasa Arab. Penelitian ini juga bertujuan menggambarkan bagaimana implementasi model komunikatif diterapkan di kelas, serta mengidentifikasi faktor-faktor pendukung dan penghambat yang memengaruhi keberhasilannya. Selain itu, penelitian ini berupaya memahami persepsi guru dan peserta didik terhadap penerapan pendekatan komunikatif sebagai bagian dari upaya peningkatan kualitas pembelajaran Bahasa Arab. Metode yang digunakan adalah pendekatan kualitatif dengan jenis studi pustaka yang diperkuat data primer dari observasi kegiatan pembelajaran, wawancara guru dan peserta didik, serta dokumentasi perangkat dan aktivitas kelas. Data sekunder diperoleh dari teori-teori Communicative Language Teaching (CLT), buku ajar, dan penelitian-penelitian sebelumnya yang relevan. Prosedur analisis mencakup reduksi data, penyajian data, interpretasi temuan, serta penarikan kesimpulan secara sistematis untuk memperoleh gambaran komprehensif mengenai efektivitas model komunikatif dalam konteks pembelajaran Bahasa Arab.Hasil penelitian menunjukkan bahwa model pembelajaran komunikatif efektif dalam meningkatkan kemampuan berbicara dan menyimak peserta didik melalui aktivitas berpasangan, role-play, permainan bahasa, diskusi kelompok, dan penggunaan media kontekstual. Peserta didik menjadi lebih percaya diri, aktif, dan mampu memahami makna dalam konteks nyata. Guru dan siswa memiliki persepsi positif terhadap pendekatan ini karena lebih menyenangkan dan relevan dengan kebutuhan komunikasi. Namun demikian, efektivitas pembelajaran dipengaruhi oleh keterbatasan kosakata, rasa malu, kecemasan berbahasa, sarana pembelajaran yang minim, serta perbedaan kemampuan antar peserta didik sehingga memerlukan strategi diferensiasi yang tepat.